Analysis of Household Income of Women Banana Chips Entrepreneurs in Unaaha City - Leni Saleh (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The purpose of this study is to analyze the income of female entrepreneurs in the banana chips business in Unaaha City, Konawe Regency. This research was conducted in Unaaha City, focusing on two female entrepreneurs who are actively engaged in the banana chips business. The sample was selected using random sampling, targeting individuals who could provide relevant data for the research. The study utilized both primary and secondary data sources to gather comprehensive information. Primary data was collected through interviews with the entrepreneurs, while secondary data was obtained from relevant records and reports. To achieve the research objectives, an income analysis method was applied to evaluate the income levels of the banana chips businesses. The findings revealed that the average monthly income from the banana chips businesses in Unaaha City was Rp 11,084,532, with a typical entrepreneur earning approximately Rp 5,542,266 per month. In comparison, the average total income was Rp 10,262,500 per month, and the average total costs amounted to Rp 4,720,234 per month. This income analysis provides insight into the economic viability of banana chips businesses operated by female entrepreneurs in Unaaha City, indicating that these businesses can generate substantial income despite challenges. The study highlights the role of female entrepreneurs in contributing to the local economy and provides valuable information for future business development strategies. Furthermore, it suggests that with proper support, such as access to training and capital, female entrepreneurs in the region can improve their business sustainability and profitability. This research could serve as a reference for similar studies and could help policymakers design programs that support small-scale female entrepreneurs in the region.